Internationalization and Quality Assurance in Higher Education - Wysocka, Karolina; Jungnickel, Christian; Szelągowska-Rudzka, Katarzyna (Zielona Góra: Faculty of Economics and Management Press)
Internationalization is an inevitable phenomenon among all contemporary higher education institutions (HEIs) in a globalizing world. It is the driving force for development and progress. In course of the last 30 years, it became an inevitable element of HE management. However, it carries along a number of risks, pitfalls, and organizational challenges. To hedge those, quality assurance (QA) is called to the stage.
Keywords: higher education; internationalization; management; quality assurance; ranking; szkolnictwo wyższe; umiędzynarodowienie; zarządzanie; zapewnienie jakości